Photoliterary Memoryscape of Tomas Espedal: Mitt privatliv (2014) – a Starting Point in a Journey to One’s Past - Wilkus-Wyrwa, Aleksandra (Scandinavistica Vilnensis, 2023)
Photography is inextricably coupled with temporal conditions. It is rooted in the past while concurrently referring to the recipient’s present and future. This article sheds light on the connection between photography, literature, and memory in Tomas Espedal’s photo book Mitt privatliv (2014; My private life). The central perspective of this paper is devoted to the link between the lyrical subject’s autobiographical memory and the individual memory of the reader. My goal is to analyze how the reader finds their point of view while confronted with the lyrical subject’s memoryscape from aesthetic, anthropological, and cognitive perspectives. Firstly, I discuss the form of Espedal’s Mitt privatliv and the book’s potential liberatic character. Secondly, in reference to François Soulages and John Berger, I show how the correlation between texts and photography affects memory functioning in a photobook. Finally, I ocus on the mechanisms of autobiographical memory, or, more precisely, how the subject’s and recipient’s memories relate to the book’s physicality, structure, and the interplay between the word and photography. Looking through the lenses of Paul Ricoeur, Aleida Assmann, and the social-communicative functions of memory, it turns out that Mitt privatliv is not just a created and closed story of a single subject; it is a story that stimulates the reader’s memory and thus impacts their understanding and constitution of their “self” in both individual and collective contexts.
Keywords: autobiographical memory; individual memory; liberature; photobook; photoliterature; Tomas Espedal